Effectiveness and safety of first-line pembrolizumab plus chemotherapy in patients with advanced/recurrent or metastatic esophageal squamous cell carcinoma in China: a real-world multicenter study - Yu Lin; Wenbin Shen; Jinjun Ye; Honglei Luo; Xizhi Zhang; Yuanji Xu; Qin Lin; Wenyang Liu; Yingying Zhang; Yujin Xu; Wei Jiang; Lina Zhao; et al. (Therapeutic Advances in Medical Oncology)
Background: There are currently limited real-world data on the effectiveness and safety of first-line pembrolizumab combined with chemotherapy in patients with advanced/recurrent or metastatic esophageal squamous cell carcinoma (ESCC) in China. This study was conducted to address this knowledge gap. Methods: This multicenter retrospective cohort study was conducted at 17 hospitals in China and included adults (⩾18 years) with stage IV primary ESCC, or recurring 6 months after radical radiotherapy/surgery-based combination therapy, who had received first-line pembrolizumab plus chemotherapy. Data were collected from electronic medical records. Endpoints included objective response rate (ORR), disease control rate (DCR) progression-free survival (PFS), overall survival (OS), and safety. Subgroup analyses were conducted to identify patient characteristics and treatment patterns associated with treatment response. Results: In total, 202 patients who had received treatment from 2018 to 2023 were included: 125 (61.9%) newly diagnosed and 77 (38.1%) with recurrence, 181 (89.1%) were male. Pembrolizumab was most commonly combined with paclitaxel + platinum (69.8%) or fluorouracil + platinum (19.3%). After a median follow-up of 22.6 months (95% confidence interval (CI) 20.1–25.4), the ORR and DCR were 60.9% and 87.6% and the median PFS and OS were 10.8 months (95% CI 9.1–13.5) and 17.3 months (95% CI 14.9–19.9), respectively. OS was similar in patients with treatment-naïve and recurrent disease. Among the combination chemotherapy regimens, paclitaxel + platinum was associated with the longest median OS (18.2 months, 95% CI 16.1–22.5). Favorable survival outcomes were observed in patients with oligometastases. No new safety signals were observed. Conclusion: These real-world data indicate that the first-line treatment with pembrolizumab plus chemotherapy is effective and safe in Chinese patients with advanced ESCC and show that paclitaxel + platinum is the most commonly used and most effective partner chemotherapy in China.